Perceived benefits of the hepatitis C peer educators: a qualitative investigation - A. W. Batchelder; L. Cockerham-Colas; D. Peyser; S. P. Reynoso; I. Soloway; A. H. Litwin (BMC, 2017)
Abstract Background Although opioid-dependent patients are disproportionately impacted by hepatitis C (HCV), many do not receive treatment. In addition to HCV treatment-access barriers, substance-using patients may be reluctant to pursue treatment because of wariness of the medical system, lack of knowledge, or stigma related to HCV treatment. Implementation of a formal peer education program is one model of reducing provider- and patient-level barriers to HCV treatment, by enhancing mutual trust and reducing stigma. Methods We used thematic qualitative analysis to explore how 30 HCV patients and peer educators perceived a HCV peer program within an established methadone maintenance program in the USA. Results Participants unanimously described the program as beneficial. Participants described the peer educators' normalization and dispelling of myths and fears around HCV treatment, and their exemplification of HCV treatment success, and reductions in perceived stigma. Peer educators described personal benefits. Conclusions These findings indicate that HCV peer educators can enhance HCV treatment initiation and engagement within opioid substitution programs.